The Comparison of Student Creative Thinking Skill using CBL Implemented in STEM Education and Combined with PSL Worksheet in Indonesian School - Noviana Putri; Dadi Rusdiana; Irma Rahma Suwarma (Universitas Pendidikan Indonesia, 2019)
The main goal of this study is to present the effectiveness improvement of student’s creative thinking skills using CBL implemented in STEM education and CBL combined with worksheet PSL. The STEM education perspective used in this study is a separate science discipline (Physics) that incorporates other disciplines. The research method used in this study is a quantitative method with a quasi-experimental research design. The research includes a pre-test-post test control group design. The subjects of the research consist of forty-five students in 10th grade of one of the vocational schools. The instrument used in this study is an essay test consisting of four questions with indicators of fluency, flexibility, and originality. The enhancement of students’ creative thinking skills is known by analyzing normalized gain (g) on the experimental group and control group. A non-parametric test and Cohen’s Kappa test were used to examine differences improvement of student’s creative thinking skills with the IBM Statistics SPSS 20.00 program at .05 significant levels. As a result of the research, it was found that CBL implemented in STEM education has a higher improvement for students of creative thinking skills than CBL combined with worksheet PSL. CBL implemented in STEM education also has a major impact on improvement of students’ creative thinking skills.